QTL analysis of textural property traits for Chinese northern-style steamed bread - Wu, Peng; Liu, Bin; Chen, Jiansheng; Sun, Cailing; Tian, Jichun (Euphytica, 2011)
Quantitative trait loci (QTLs) influencing textural properties (hardness, adhesiveness, springiness, cohesiveness, gumminess, chewiness, and resilience)of wheat for Chinese northern-style steamed bread were studied using a doubled haploid (DH) population containing 168 lines derived from a cross between elite Chinese wheat cultivars Huapei 3 and Yumai 57 ( Triticum aestivum L . ). The DH population and parents were grown in 2007 and 2008 in Tai’an and 2008 in Suzhou. QTL analyses were performed using the software QTL Network version 2.0 and IciMapping v2.2 based on the mixed linear model. Thirty nine putative QTLs were detected on 14 chromosomes: viz. 1A, 2A, 3A, 4A, 6A, 1B, 2B, 3B, 5B, 6B, 7B, 5D, 6D, and 7D, and single QTLs explained 3.91–35.17% of the phenotypic variation. Eight pairs of QTLs with epistatic effects and/or epistasis × environment (AAE) effects were detected for adhesiveness, resilience, hardness, and cohesiveness on chromosomes 2A, 1B and 3D. Several co-located QTLs with additive effects were detected on chromosomes 2B, 5D, 6A, 3A, 3B and 6D. Two clusters of three QTLs for steamed bread textural properties (chewiness, gumminess, and hardness) and for adhesiveness, cohesiveness and resilience were detected on chromosome 2B. Two co-located QTLs with epistatic effects were detected on chromosomes 1B and 3A. Both additive effects and epistatic effects were important for Chinese steamed bread textural properties, which were also subject to environmental modifications. The information obtained in this study will be useful for manipulating QTLs determining Chinese steamed bread textural properties by molecular marker-assisted selection.